Keanekaragaman lalat buah (Diptera: Tephritidae) dan parasitoidnya di Taman Buah Mekarsari, Cileungsi, Bogor - Ardiyanti, Rizky Marcheria; Maryana, Nina; Pudjianto, Pudjianto (Jurnal Entomologi Indonesia, 2019)
Fruit fly (Diptera: Tephritidae) is one of the important pest in horticultural plants which can cause quantitative and qualitative losses of production. One of the potential natural enemies to control the fruit flies is parasitoid. The aim of this research was to study the diversity of fruit flies and its parasitoids in Mekarsari Fruit Garden. The research was carried out in March to August 2017. Identification of fruit flies and parasitoids was conducted at Insect Biosystematics Laboratory, Institut Pertanian Bogor. Fruit flies were collected by setting Steiner traps and collecting infested fruits. In each sampling point, two traps were installed useing two different attractants, i.e. methyl eugenol (ME) and cue lure (CL). Steiner traps were set up for six weeks and the trapped fruit flies were taken every week. Collected fruits were 1 kg for each fruits species, within 1-6 timed depend on fruit existence. Based on ME attractants, 4 species of fruit flies were identified, i.e. Bactrocera (B.) carambolae, B. (B.) umbrosa, B. (B.) dorsalis, and B. (B.) occipitalis, while 6 species were attracted by CL, i.e. B. (B.) albistrigata, B. (Z.) calumniata, B. (Z.) caudata, B. (Z.) cucurbitae, B. (Z.) tau, and D. (C.) longicornis. Three parasitoids (Hymenoptera: Braconidae) were found from rotting fruits, i.e. Diachasmimorpha longicaudata (Ashmead), Fopius arisanus (Sonan), and F. vandenboschi Fullaway.